Iron speciation in aerosol dust influences iron bioavailability over glacial‐interglacial timescales. Issue 8 (27th April 2013) - Spolaor, A.; Vallelonga, P.; Cozzi, G.; Gabrieli, J.; Varin, C.; Kehrwald, N.; Zennaro, P.; Boutron, C.; Barbante, C.
Abstract : [1] Iron deposition influences primary production and oceanic sequestration of atmospheric carbon dioxide (CO2 ). Iron has two oxidation states, Fe(II) and Fe(III), with Fe(II) being more soluble and available for oceanic phytoplankton uptake. The past proportions of soluble iron in aerosol dust remain unknown. Here we present iron speciation (Fe 2+ and Fe 3+ ) in the Antarctic Talos Dome ice core over millennial time scales. We demonstrate that iron speciation over the last 55 kyr is linked to increasing quantities of fine dust (FD) (0.7–5 µm) and intensified long‐range dust transport. We propose that Fe(II) and Fe 2+ production is principally enhanced in FD by photoreduction, although pH and organic complexation may also contribute to the speciation dynamics. During the Last Glacial Maximum, Fe 2+ concentrations in dust increased by up to seven times more than interglacial levels, while Fe 3+ only doubled. Cold and dusty climatic periods may increase the percentage of biologically available Fe(II) and Fe 2+ deposited in the nutrient‐limited Southern Ocean, allowing greater phytoplankton uptake and perhaps increased CO2 drawdown. Key Points: The first work recording iron speciation in ice core in glacial‐interglacial Importance of iron species in the bioavailability of iron It demonstrates that the addition of iron species results in CO2 drawdown